A Study on the Efficiency of Capital Markets in India - Nanjundappa, Deepak (2009)
The study on the efficiency of capital markets has been one of the most widely selected topics for research. It provides an understanding of how the capital market works. Market efficiency usually influences the investment strategy of an investor. The efficient market does not allow investor to beat the market as the information is reflected in the price and information is easily available to all the investors. This study examines the efficiency of the capital markets in India and shows that it is weak form efficient. Various tests are carried out to test the random walk nature and the efficiency of the capital market. The results are carefully observed and interpreted.